Complete mitochondrial genomes provide current refined phylogenomic hypotheses for relationships among ten Hirundo species. Issue 3 (2nd July 2020) - Carter, Javan K.; Innes, Peter; Goebl, April M.; Johnson, Benjamin; Gebert, Matthew; Attia, Ziv; Gabani, Zachariah; Li, Ruiqi; Melie, Tina; Dart, Chiara; Mares, Ali; Greidanus, Chrisopher; et al.
Abstract: Hirundo is the most species-rich genus of the passerine swallow family (Hirundinidae) and has a cosmopolitan distribution. Here we report the complete, annotated mitochondrial genomes for 25 individuals from 10 of the 14 extant Hirundo species; these include representatives from four subspecies of the barn swallow, H. rustica . Mitogenomes were conserved in size, ranging from 18, 500 to 18, 700 base pairs. They all contained 13 protein-coding regions, 22 tRNAs, a control region, and large and small ribosomal subunits. Phylogenetic analysis resolved most of the relationships between the studied species and subspecies which were largely consistent with previously published trees. Several new relationships were observed within the phylogeny that could have only been discovered with the increased amount of genetic material. This study represents the largest Hirundo mitochondrial phylogeny to date, and could serve as a vital tool for other studies focusing on the evolution of the Hirundo genus.